Assessing Anti-HCMV Cell Mediated Immune Responses in Transplant Recipients and Healthy Controls Using a Novel Functional Assay - Houldcroft, Charlotte J.; Jackson, Sarah E.; Lim, Eleanor Y.; Sedikides, George X.; Davies, Emma L.; Atkinson, Claire; McIntosh, Megan; Remmerswaal, Ester B. M.; Okecha, Georgina; Bemelman, Frederike J.; Stanton, Richard J.; Reeves, Matthew; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
HCMV infection, reinfection or reactivation occurs in 60% of untreated solid organ transplant (SOT) recipients. Current clinical approaches to HCMV management include pre-emptive and prophylactic antiviral treatment strategies. The introduction of immune monitoring to better stratify patients at risk of viraemia and HCMV mediated disease could improve clinical management. Current approaches quantify T cell IFNγ responses specific for predominantly IE and pp65 proteins ex vivo, as a proxy for functional control of HCMV in vivo. However, these approaches have only a limited predictive ability. We measured the IFNγ T cell responses to an expanded panel of overlapping peptide pools specific for immunodominant HCMV proteins IE1/2, pp65, pp71, gB, UL144, and US3 in a cohort of D+R– kidney transplant recipients in a longitudinal analysis. Even with this increased antigen diversity, the results show that while all patients had detectable T cell responses, this did not correlate with control of HCMV replication in some. We wished to develop an assay that could directly measure anti-HCMV cell-mediated immunity. We evaluated three approaches, stimulation of PBMC with (i) whole HCMV lysate or (ii) a defined panel of immunodominant HCMV peptides, or (iii) fully autologous infected cells co-cultured with PBMC or isolated CD8+ T cells or NK cells. Stimulation with HCMV lysate often generated non-specific antiviral responses while stimulation with immunodominant HCMV peptide pools produced responses which were not necessarily antiviral despite strong IFNγ production. We demonstrated that IFNγ was only a minor component of secreted antiviral activity. Finally, we used an antiviral assay system to measure the effect of whole PBMC, and isolated CD8+ T cells and NK cells to control HCMV in infected autologous dermal fibroblasts. The results show that both PBMC and especially CD8+ T cells from HCMV seropositive donors have highly specific antiviral activity against HCMV. In addition, we were able to show that NK cells were also antiviral, but the level of this control was highly variable between donors and not dependant on HCMV seropositivity. Using this approach, we show that non-viraemic D+R+ SOT recipients had significant and specific antiviral activity against HCMV.